PENGARUH CONTENT MARKETING DAN SOCIAL MEDIA YOUTUBE 3SECOND TV TERHADAP MINAT BELI PRODUK 3SECOND - Septiawan, Redho Dwi; De Yusa, Viola (LPPM Politeknik Pratama, 2023)
The rapid advancement of technology has an impact on aspects of life that affect customer buying behavior from traditional shopping to online shopping. Many thoughts are in the form of creative and innovative ideas or ideas from marketers to succeed or win competition in the market, one of which is by creating content marketing. The purpose of this research is to understand how social media and content marketing on YouTube 3second TV influence the intention to buy 3second products. The sample used for this study consisted of 100 people who were respondents as potential customers and consumers of 3seconds products. Purposive sampling was used in this sampling procedure. In this research methodology used multiple linear analysis. Microsoft Excel and SPSS 24 were used to analyze the survey data. The results of the study show that there is a relationship between content marketing variables (X1) and social media (X2) with buying interest (Y).